Standing weight-bearing distribution behavior in people with chronic hemiparesis: review and meta-analysis - Camargos, Monike Barros; Pinheiro, Hudson Azevedo; Rabelo, Michelle; Baptista, Roberto de Souza; Fachin-Martins, Emerson (Journal of Health Care, 2016)
Although it has been reported that people with chronic hemiparesis present asymmetric distribution of weight in the standing position, some evidences also show symmetric distribution in this population. This review aimed to collect researches investigating weight-bearing distribution in the standing position on patients with hemiparesis after stroke, identifying which weight-bearing behavior has been described by authors for this population. PUBMED, EMBASE, COCHRANE, CINAHL and SCIELO databases were consulted until October 2015. It was highlighted from the selected references the following information: (1) measurements of weight-bearing distribution, (2) devices used to measure this distribution, (3) available information about psychometric properties of the device used and (4) presented concept of weight-bearing distribution. Among the references collected, those presenting data obtained by digital scales and allowing calculation of symmetry ratio were used for meta-analysis. In most of studies, as previous mentioned, prevailed the concept that subjects with chronic hemiparesis have asymmetric distribution overloading non-paretic hemibody. However, the heterogeneity among studies, the lack of parameters to define weight-bearing symmetry and little information about psychometric properties of the devices used show the necessity of further investigation.